Direct crosstalk between adult human retinas as suggested by interocular transfer of neurovascular coupling through photic stimulation - João Jordão; João Figueira; Miguel Morgado; Pedro Guimarães; Pedro Serranho; Daniela Castro-Farías; Delia Cabrera DeBuc; Miguel Castelo-Branco; Michel Paques; Rui Bernardes (Scientific Reports)
Abstract Crosstalk mechanisms between retinas were never documented in humans despite being documented for several other species, including non-human primates. Results of the first-in-human study that documents the crosstalk between retinas by measuring the vascular response in one retina to the photic stimulation of the contralateral eye in health and disease are reported herein. A stimulation apparatus was developed and integrated into an adaptive-optics fundus camera to image 32 healthy control (HC) subjects and 20 type 1 diabetes mellitus (DM) patients. Ipsilateral and contralateral neurovascular coupling effects were documented, and criteria were established to consider an actual response and find positive and negative responses. Ten (31.2%) and two (6.2%) subjects of the HC group presented contralateral positive and negative responses, respectively, and three (15.0%) positive and four (20.0%) negative responses were found for the DM group. Also, statistically significant differences in the ipsilateral (p < 0.001) and contralateral (p = 0.027) responses were found for the HC group, rejecting the null (non-response) hypothesis. This finding raises the need to revisit the current knowledge of neurovascular coupling mechanisms and the association between its dysregulation and neurological disorders. Further studies involving distinct populations and imaging centers are necessary to validate the findings herein.